2018
DOI: 10.1007/s00432-018-2690-9
|View full text |Cite
|
Sign up to set email alerts
|

The clinical usefulness of optical coherence tomography during cancer interventions

Abstract: IntroductionTumor detection and visualization plays a key role in the clinical workflow of a patient with suspected cancer, both in the diagnosis and treatment. Several optical imaging techniques have been evaluated for guidance during oncological interventions. Optical coherence tomography (OCT) is a technique which has been widely evaluated during the past decades. This review aims to determine the clinical usefulness of OCT during cancer interventions focussing on qualitative features, quantitative features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 148 publications
(177 reference statements)
1
35
0
1
Order By: Relevance
“…OCT is a technique often compared to ultrasound. However, instead of sound pulses emitted and received by the ultrasound probe, an OCT probe typically emits near-infrared light pulses in to the tissue and detects the back-reflected light [259]. Spatial resolution of this technique is in the order of μm's.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…OCT is a technique often compared to ultrasound. However, instead of sound pulses emitted and received by the ultrasound probe, an OCT probe typically emits near-infrared light pulses in to the tissue and detects the back-reflected light [259]. Spatial resolution of this technique is in the order of μm's.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Optical coherence tomography (OCT) is a label-free optical technique based on low coherence light interferometry allowing for fast cross-sectional views of tissue structure [9][10][11]. As this method is non-invasive, non-destructive and label-free it has found broad application in diagnostic of different types of skin cancer, oral cancer, lung cancer, breast cancer, colon cancer, prostate cancer and esophageal cancer [12]. Yuan et al showed a combined OCT and ultrasound approach to investigate bladder cancer in a rat model [13].…”
Section: Introductionmentioning
confidence: 99%
“…When compared to other modalities such as conventional OCT or even confocal microscopy, FF-OCT was demonstrated to significantly improve spatial resolution by a factor varying from five to ten depending on the acquisition axis [21]. Until now, most groups have focused on the potential role of FF-OCT during oncologic interventions as new routine approach to surgical pathology [22], and, except for one preliminary study in which the superficial temporal arteries were imaged with dermal OCT [23], there has been no reported attempt to employ high definition interference microscopy for the pathological diagnosis of GCA. The present work pursues the hypothesis that FF-OCT could help both the clinician and pathologist to improve TAB performance, and compares, for the first time, FF-OCT and conventional histological examination for the pathological diagnosis of GCA.…”
Section: Introductionmentioning
confidence: 99%